Clinical use of resuscitative endovascular balloon occlusion of the aorta (REBOA) in civilian trauma systems in the USA, 2019: a joint statement from the American College of Surgeons Committee on Trauma, the American College of Emergency Physicians, the National Association of Emergency Medical Services Physicians and the National Association of Emergency Medical Technicians. Issue 1 (20th September 2019) - Bulger, Eileen M; Perina, Debra G; Qasim, Zaffer; Beldowicz, Brian; Brenner, Megan; Guyette, Frances; Rowe, Dennis; Kang, Christopher Scott; Gurney, Jennifer; DuBose, Joseph; Joseph, Bellal; Lyon, Regan; et al.
Abstract : This is a joint statement from the American College of Surgeons Committee on Trauma, the American College of Emergency Physicians, the National Association of Emergency Medical Services Physicians and the National Association of Emergency Medical Technicians regarding the clinical use of resuscitative endovascular balloon occlusion of the aorta (REBOA) in civilian trauma systems in the USA. This statement addresses the system of care needed to manage trauma patients requiring the use of REBOA, in light of the current evidence available in this patient population. This statement was developed by an expert panel following a comprehensive review of the literature with representation from all sponsoring organizations and the US Military. This is an update to the previous statement published in 2018. It has been formally endorsed by the four sponsoring organizations.